HUBUNGAN MOTIVASI BELAJAR DAN DISIPLIN DENGAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI SMA PERGURUAN ISLAM CERDAS MURNI DELI SERDANG KECAMATAN PERCUT SEI TUAN - Aminah Hasibuan (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: This research is proposed to know: 1.The correlation motivation of studying on the resultsstudying of learning islamic religious education in SMA Cerdas Murni Deli Serdang sub district percut seituan, 2. The correlation discipline of studying on the results studying of learning islamic religious educationin SMA Cerdas Murni Deli Serdang sub district percut sei tuan,, 3.The correlation motivation ofstudying and discipline. on the results studying of learning islamic religious education in SMA CerdasMurni Deli Serdang sub district percut sei tuan. There are three finds of research: First, motivation ofstudying have correlation of the results studying of learning islamic religious education in SMA CerdasMurni Deli Serdang sub district percut sei tuan (r_y1 = 0.376) to a = 0,05. This case shows that themotivation of studying increasing, so there is an increasing of the results studying of learning islamicreligious education in SMA, and the motivation studying so the less of the results studying of learningislamic religious education in SMA Cerdas Murni Deli Serdang sub district percut sei tuan.